Pengaruh Promosi Dan Kualitas Pelayanan Terhadap Keputusan Konsumen Dalam Menggunakan Layanan Grabfood Di Batam - Serni Sari Septiati; Triana Ananda Rustam (eCo-Buss, 2022)
The study aimed to look out is it promotion and service qualiy affect the consument decision of using Grabfood service in Batam. Data collecting technique is by used by spreading out a whole list of questioner up to 138 respondant. data then analyzed using test of validity, reliable test, normal test, multicolinearity test, heterocedasticity test, multiple liniarregresion analytict, coeficient of determination analytic, t test and F test by using the help of software SPSS 26. This test obtained a calculated f value of 125.128, with table F the magnitude is 2.67. In this test, the relationship of all promotion, the quality of service on customer decision was fulfilled. This statement is supported by the calculated F which is higher than the F table, and the significant value is 0.000 which is fewer than 0.05. and that gave a conlusion that the promotion and service quality affect customer decision of using Grabfood service.